ANALISIS PEMBELAJARAN MATA KULIAH PENDIDIKAN BAHASA DAERAH PADA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR (PGSD) - Suhadah; Kuswaty, Maya; Avi Valentri (Desanta Publisher, 2025)
This study aims to analyze the learning process of the Local Language Education course in the Primary School Teacher Education (PGSD) program. The research method used is qualitative with a descriptive approach. The findings indicate that this course plays a crucial role in preserving local languages and instilling cultural values in students. However, several challenges are encountered, such as limited exposure to local languages in daily life, insufficient digital-based learning materials, and a lack of educators with specialized competencies in this field. To address these challenges, various strategies have been implemented, including the use of digital technology in learning, collaboration with cultural experts and native speakers, and project-based learning methods. The implications of this study suggest that strengthening local language education through innovative strategies can enhance students' competencies and contribute to the broader preservation of local languages in both academic and societal contexts.